Threat of deportation as proximal social determinant of mental health amongst migrant workers - Nicholas HARRIGAN, (Institutional Knowledge at Singapore Management University, 2017)
While migration health studies traditionally focused on socioeconomic determinants of health, an emerging body of literature is exploring migration status as a proximate cause of health outcomes. Study 1 is a path analysis of the predictors of mental health amongst 582 documented migrant workers in Singapore, and shows that threat of deportation is one of the most important proximate social determinants of predicted mental illness, and a mediator of the impact of workplace conflict on mental health. Study 2 is a qualitative study of the narratives of 149 migrant workers who were in workplace conflict with their employers, and demonstrates that workers believed threats were used as a negotiating strategy during workplace conflicts. Findings suggest that migration status places workers who come into workplace conflict with their employers at heightened risk of mental illness because migration status can be used as a tool by employers in workplace negotiations.